(untitled) (Pubmet, 2023)
Introduction and aim: Scientific journals are a key communication channel for the transmission of scientific information, and the publication of articles is mandatory in scientific advancements. Open access publishing enables greater visibility of scientific outputs but publication in open access is rarely free (Van Norden, 2013; Pourret 2022). The aim of this research is to examine the article processing charges (APCs) of journals in the Health professions category within the SCOPUS database, along with their respective business models (hybrid, OA or diamond OA). Methods: We collected data on journals using Scimago, DOAJ and Sherpa Romeo databases, as well as the homepages of journals and publishers. Using the SCImago Journal & Country Rank data for the year 2022, we filtered journals belonging to the field and category of "Health Professions (miscellaneous)". Data were gathered on the number of journals in Scopus, the type of journal (hybrid, open access, diamond journal) and the cost for publishing (APC) an original scientific article/review article in open access. Information about the type of the journal was collected in Sherpa Romeo/DOAJ databases, information on the APCs was found on the pages of the journal or publisher. Results: A total of 60 journals belonging to the category of Health professions in Scopus were identified, with 28 (47%) of them also in the Web of Science database according to Scimago. Of these 60 journals, 28 are hybrid journals, 32 are in open access (53%), including 10 in open access with an APC, and 22 completely free - diamond journals. The publication cost in all journals is in the range from €0 to €3,385.00, with an average median price of €788 (ranging from €0 to €2,895). The average APC is significantly lower in open access journals than in hybrid journals (median €881, ranging from €92 to €2466, versus €2895, ranging from €2045 to €2977), which is in line with previously published results in the medical field (Siler et al, 2018). Most of the diamond journals are in the 3rd (6 out of 22) and 4th quartiles (9 out of 22) or have only recently (3 out of 22) been included in the Scopus database. Limitations of the study: The study sample is small, and has only 60 journals, while there could be more journals connected with health professions in other Scopus categories. Information about waivers was not collected. Conclusion: Journals of the 1st and 2nd quartile, which are considered an important criterion for advancement in the biomedical field, are mostly hybrid journals and the APCs are very high. Consequently, the conclusion emerges that health professions do not have a large selection of journals for publishing in open access, and therefore it is necessary to educate authors to self-archive their articles.